Planning a WIC Research Agenda : Workshop Summary - Suitor, Carol West (National Academies Press, 2011)
"To guide its planning for the use of the $15 million allocated for WIC research, the Food and Nutrition Service of USDA asked the Institute of Medicine to conduct a two-day public workshop on emerging research needs for WIC. As requested, the workshop included presentations and discussions to illuminate issues related to future WIC research issues, methodological challenges, and solutions. The workshop also planned for a program of research to determine the effects of WIC on maternal and child health outcomes."--Publishers website.